Die gemolesteerde kind as getuie - Grey, E. (Koers, 1991)
The accusatorial principle provides the basis for the South African taw o f criminal procedure. In practice this results in the abused child being subjected to substantial trauma when it is called upon to give evidence in such a case. The abused child is often still battling to regain its self-esteem and self-confidence at the time of the trial. By subjecting the abused child to the giving of vidence and being cross-examined in the presence of the accused, the child's chances of regaining its selfesteem are rendered very slim indeed. In the interest of the abused child, and to satisfy the requirement of justice for all, an alternative to the existing system has to be found. In order to improve on the current situation, it is the author’s submission that a form of procedure should be adopted through which the appearance of the abused child in court during such a trial will be obviated. Some specific proposals to achieve this are made by the author.